The design of "Grain Boundary Engineered" architected cellular materials: The role of 5-7 defects in hexagonal honeycombs. (15th January 2023) - Yu, B.; Aranguren van Egmond, D.; Abu Samk, K.; Erb, U.; Wilkinson, D.; Embury, D.; Zurob, H.
Abstract: Inspired by heterogeneous structures observed in nature (graphene, insects' eyes, and beehives), we demonstrate that topological defects in hexagonal honeycombs can enhance strength and energy absorption capacity. These defects consist of pentagon-heptagon pairs (known as 5–7 defects). Experimental studies of additive manufactured specimens and computational studies are performed on honeycomb panels that are perfectly periodic or that contain defects in one of two arrangements: (i) clustered to form inclusions or (ii) aligned to form 5–7 domain boundaries. The focus is on the compressive response in out-of-plane, in-plane, and inclined orientations. The results show a 25–30% strength improvement when the 5–7 defects are arranged into aligned domain boundaries. The boundaries induce asymmetric deformation and hydrostatically reinforce the neighbouring hexagonal cells. Such effects can be attributed to differences in topological network adjacency. The results suggest that there remains a largely untapped design space involving heterogeneous cellular structures. Graphical abstract: Image, graphical abstract